A new species of dactyloid anole (SQUAMATA: IGUANIDAE) from the western Andes of Ecuador - Ayala-Varela, Fernando P.; Velasco, Julián Andrés (Zootaxa, 2010)
We describe a new species of Anolis from the western slopes of the Andes in Ecuador, Provincias Cotopaxi and Pichincha. The new species fits into (1) the aequatorialis species group by being of moderate to large size with narrow toe lamellae and (2) the eulaemus subgroup by having a typical Anolis digit, in which the distal lamellae of phalanx II distinctly overlap the proximal scales of phalanx I. The new species is most similar to A. gemmosus O’Shaughnessy but differs from it by features like the presence of a dark coppery brown stripe on the sides of the head (stripe absent in A. gemmosus), females with dark brown dorsal chevrons extending to the flanks (chevrons absent in A. gemmosus), male dewlap white with green scales (male dewlap greenish-yellow with green scales in A. gemmosus), dewlap with wide scale rows of three to six scales per row (narrow scale rows of 2−3 scales per row in A. gemmosus), and interparietal scale (if present) surrounded by relatively enlarged flat scales (interparietal surrounded by small swollen scales in A. gemmosus). These two species occur in sympatry in the Reserva de Bosque Integral Otonga, Provincia Cotopaxi, Ecuador.